Restoration of Degraded Tropical Rain Forests of Western Ghats - Rai, S. N. (Indian Forester, 1990)
The Tropical Rain Forests in India are found in the Western Ghats. In North-east Region and in the Andaman and Nicobar Islands. The Western Ghats have seasonal rainfall which may range from 2000-8000 mm; number, of rainy months decrease from 8 to 4 from Kanyakumari (Tamil Nadu) to Mahabaleswar (Maharashtra). There is high temperature in summer and rainfall is concentrated in three rainy months. Two important factors namely; the degree of slope and distribution of rainfall, not only determine the species composition but also determine the change in site conditions consequent to degradation. Efforts of restoration are also determined eventually by these factors. These are the factors that determine the type of colonisers that come up in these areas; which further depends upon the microclimate and size of the opening. Trials of the past on restocking of Tropical Rain forests have given out certain interesting results. 1-Most typical species of these forest have capacity to continue to survive under full overhead shade over a long period of time (20-25 years) without any appreciable growth, however they respond to light when available and resume their growth in a normal fashion 2-Planting or seral species is a more desirable effort in degraded rain forests, which have remained as such for some period of time. However, eventually only the main evergreen species succeed. 3-It is possible, to adequately regenerate the Tropical Rain Forest species under plantation condition with good care on sites which are not prone to soil erosion. 4-Rate of growth under shade conditions is rather slow.